2017
DOI: 10.4274/balkanmedj.2016.1114
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Inflammatory Biomarkers and Left Ventricular Systolic Dysfunction in Patients with Exacerbations of Chronic Obstructive Pulmonary Disease

Abstract: Background:Cardiovascular diseases are an important cause of morbidity and mortality in chronic obstructive pulmonary disease patients. The increased inflammatory biomarker levels predict exacerbations and are associated with cardiovascular diseases in stable chronic obstructive pulmonary disease patients but their role in the settings of acute chronic obstructive pulmonary disease exacerbations has not been determined.Aims:To analyse the association between inflammatory biomarkers and heart failure and also t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
(18 reference statements)
0
9
1
Order By: Relevance
“…In clinical practice, septic cardiomyopathy (S-CMP) has been regarded as a poorly understood phenomenon with a variety of underlying mechanisms-including detrimental impacts of cytokines and nitric oxide on the myocardium-and generally presents with emerging systolic and/or diastolic dysfunction on transthoracic echocardiogram (TTE) in septic patients (1)(2)(3). Within this context, the association of inflammation markers, in particular, with left ventricular systolic dysfunction might also be substantiated by previous reports in diverse clinical scenarios other than sepsis (4). Interestingly, S-CMP, though renowned for its reversible nature (1), might not fully recover in certain settings, potentially suggesting some degree of permanent myocardial injury (3).…”
mentioning
confidence: 81%
“…In clinical practice, septic cardiomyopathy (S-CMP) has been regarded as a poorly understood phenomenon with a variety of underlying mechanisms-including detrimental impacts of cytokines and nitric oxide on the myocardium-and generally presents with emerging systolic and/or diastolic dysfunction on transthoracic echocardiogram (TTE) in septic patients (1)(2)(3). Within this context, the association of inflammation markers, in particular, with left ventricular systolic dysfunction might also be substantiated by previous reports in diverse clinical scenarios other than sepsis (4). Interestingly, S-CMP, though renowned for its reversible nature (1), might not fully recover in certain settings, potentially suggesting some degree of permanent myocardial injury (3).…”
mentioning
confidence: 81%
“…In clinical practice, septic cardiomyopathy (S-CMP) has been regarded as a poorly understood phenomenon with a variety of underlying mechanisms-including detrimental impacts of cytokines and nitric oxide on the myocardium-and generally presents with emerging systolic and/or diastolic dysfunction on transthoracic echocardiogram (TTE) in septic patients (1)(2)(3). Within this context, the association of inflammation markers, in particular, with left ventricular systolic dysfunction might also be substantiated by previous reports in diverse clinical scenarios other than sepsis (4). Interestingly, S-CMP, though renowned for its reversible nature (1), might not fully recover in certain settings, potentially suggesting some degree of permanent myocardial injury (3).…”
mentioning
confidence: 81%
“…Andrijevic et al reported that the most common CVDs associated with AECOPD were arterial hypertension (77.8%), systolic dysfunction (24.2%) and coronary artery disease (14.9%). Mortality was higher in patients with systolic dysfunction (19.2%) compared with subjects who had preserved ejection fraction (4.8%) …”
Section: Comorbiditiesmentioning
confidence: 93%
“…Mortality was higher in patients with systolic dysfunction (19.2%) compared with subjects who had preserved ejection fraction (4.8%). 96 In a large-scale study Jones et al 97 investigated the correlation between CVD and exacerbation rates and mortality in COPD cohort. They concluded that the presence of CVD was not associated with increased risk of exacerbations or death, but with a higher risk of hospitalisation.…”
Section: Cardiovascular Diseasementioning
confidence: 99%